Correlation between coagulation and inflammation state in patients with diabetes mellitus type 2 in relation to gender differences: is there any impact of eight-week exercise training? - Trebinjac, Divna; Petronic, Ivana; Lalic, Nebojsa; Nikolic, Dejan (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The hypercoagulable state and inflammation state in diabetics has been widely studied by previous researchers, but there is a lack of research about a possible impact of exercise training on this relationship. The aim of this study was to assess and compare correlation between the coagulation and inflammation status in patients with type 2 diabetes mellitus taking into account the gender differences as well as an impact of the 8-week exercise training on the correlation coefficient and parameters of the inflammation and coagulation state. Methods. A total of 60 patients in stable clinical condition and well-regulated diabetic status passed through all phases of the study. The exercise training included the exercise program as interval training with estimated intensity uphill to 75% of a maximal heart rate in particular individual, 5 times a week for 8 weeks, and walking for 30 minutes with a speed of 5 km/h, 5 times a week for 8 weeks. Further fibrinolytic, coagulation and inflammatory parameters were analyzed before and after the study: D-dimer, von Willebrand factor (vWF), fibrinogen, high sensitivity CRP (hs-CRP), leukocytes, thrombin time (TT), prothrombin time (PT), activated partial thromboplastin time (APTT) and coagulation factors: FII, FV, FVII and FX. Results. Our research showed a statistically significant reduction in the mean vWF levels after intervention both at the males (p
Keywords: diabetes mellitus, type 2; blood coagulation; inflammation; exercise; sex